Review of the Fund's Income Position for FY 2018 and FY 2019-20. (Policy Papers; Policy Paper ;, 2018)
The Fund's total net income for FY 2018 is projected at about SDR 0.7 billion, broadly in line with the April 2017 estimate. The projections for total lending income are broadly unchanged. Most sources of lending income are lower, reflecting a lower level of credit outstanding as a result of advance repurchases and delayed disbursements. However, projected commitment fee income is higher following the early cancellation of a large FCL arrangement in November 2017. The paper recommends that GRA net income of SDR 0.7 billion for FY 2018 (excluding projected income of the gold sales profits-funded Endowment Subaccount) be placed to the special and general reserve. After the placement of GRA FY 2018 net income to reserves, precautionary balances are projected to reach SDR 17.4 billion at the end of FY 2018. The paper further proposes to transfer currencies equivalent to the increase in the Fund's reserves from the GRA to the Investment Account. The paper also revisits options for the allocation of net income between the special and general reserve, and proposes that net income be allocated equally between the special and general reserve. In line with the recent Board discussion of a framework for guiding future payouts from the Endowment Subaccount, the paper presents a detailed proposal, which includes delaying payouts for three years to protect the real value of the Endowment. The paper also recommends that the margin for the rate of charge for the period FY 2019-2020 be kept unchanged at 100 basis points. The margin will again be set under the exceptional circumstances clause, as non-lending income continues to be constrained by the low interest rate environment and lending income will be used to finance a portion of the Fund's non-lending activities. The projections for FY 2019 and FY 2020 point to a net income position of SDR 0.4 billion and SDR 1 billion, respectively. These projections are subject to considerable uncertainty and are sensitive to a number of assumptions.